A new species and a new record of Sphaeroma Bosc, 1802 (Sphaeromatidae: Isopoda: Crustacea) from intertidal marine habitats of the Persian Gulf - Khalaji-Pirbalouty, Valiallah; Wägele, Johann-Wolfgang (Zootaxa, 2010)
Two species of Sphaeroma (Sphaeromatidae: Isopoda) from the Iranian coasts of the Persian Gulf were studied and described. Sphaeroma khalijfarsi sp. nov. is described from the intertidal zone of the Strait of Hormuz. This species is distinguished by the smooth pereonites; pleon without prominent tubercles and bearing some scattered small tubercles; pleotelson with numerous scattered small tubercles and well upturned posterior margins. Sphaeroma walkeri Stebbing, 1905 is reported from Kish and Qeshm Islands and from the southern coasts of Iran. Among the non-Indian Ocean species, Sphaeroma intermedium Baker, 1926 is transferred to genus Lekanesphera Verhoeff, 1943.